Obsessive–Compulsive Tendencies Are Related to a Maximization Strategy in Making Decisions - Oren, Ela; Dar, Reuven; Liberman, Nira (Frontiers in Psychology, 2018)
The present studies were motivated by the hypothesis that attenuated access to internal states in obsessive-compulsive (OC) individuals, which leads to extensive reliance on external proxies, may manifest in a maximizing decision making style, i.e., to seeking the best option through an exhaustive search of all existing alternatives. Following previous research, we aimed to explore the possible relationships between OC tendencies, seeking proxies for internal states, indecisiveness and maximization. In Study 1, we measured levels of OC tendencies, seeking proxies for internal states, indecisiveness, maximization, depression and anxiety in an online Hebrew speaking sample (N = 201). In Study 2, we administrated the same questionnaires to an online English speaking sample (N = 240) and in addition, examined participants’ decision making strategies in a hypothetical situation. The participants in both studies were unscreened adults. Correlational and linear regressions analyses indicated that OC tendencies are related to maximization, even when levels of indecisiveness, depression and anxiety are controlled for. Moreover, the findings suggested that reliance on external proxies may partially account for the aforementioned association. Possible implications and future directions are discussed.